2012
DOI: 10.1364/oe.20.003954
|View full text |Cite
|
Sign up to set email alerts
|

Precise and rapid distance measurements by scatterometry

Abstract: We found that the distances between isolated scatterers with similar columnar shapes could be measured by taking a single Fourier transform of their diffraction intensity. If the scatterers have different shapes, the distances between similar shapes can be selected from the distances between all the shapes. The distance from a specific scatterer can be measured with a resolution of 0.8 wavelengths and a precision of 0.01 wavelengths. This technique has the potential to be used in a novel optical memory that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…To calculate scattering with directional information, a large left scatterer was added. It has a strong scattering intensity, because the scattering intensity increases as the scatterer becomes larger [17]. The result of FT is shown in Fig.…”
Section: Array Of Columns For High-density Memorymentioning
confidence: 97%
See 4 more Smart Citations
“…To calculate scattering with directional information, a large left scatterer was added. It has a strong scattering intensity, because the scattering intensity increases as the scatterer becomes larger [17]. The result of FT is shown in Fig.…”
Section: Array Of Columns For High-density Memorymentioning
confidence: 97%
“…Itoh et al proposed the model of memory shown in Fig. 1a [17]. This model has the following characteristics.…”
Section: Array Of Columns For High-density Memorymentioning
confidence: 99%
See 3 more Smart Citations